An approach to describe the shear-thickening viscosity of cement paste incorporating microfines of manufactured sand. (18th July 2022) - Zhu, Jiang; Xie, Weixiao; Li, Zhen; Liu, Jiaping; Ran, Qianping; Li, Xiaolong; Tang, Jinhui; Shu, Xin
Highlights: Shear-thickening viscosity can increase despite reduced shear thickening performance. The thickening viscosity at a fixed flow increases due to enhanced particle contacts. Particle contact interactions in shear thickening regime increase with flow index. A model of the thickening viscosity is developed given particle contacts and inertia. Abstract: This paper investigates the mechanisms affecting the viscosity in shear thickening regimes of cement pastes. Limestone, slate, and tuff microfines (≤125 μm) with different physical properties obtained in the processing of manufactured sand were employed as additional mineral materials to cement pastes prepared with variable dosages of polycarboxylate ether superplasticizer (PCE) and water-to-cement mass ratios (W/C) of 0.40 and 0.275. Test results show that the addition of microfines reduced the shear thickening properties of cement pastes at a fixed PCE dosage, mainly due to a smaller growth of particle inertial interactions from the pseudo-Newtonian plateau to a given shear rate. But the shear thickening reduction did not always cause a lower increase of the apparent viscosity, Δ η thic γ ̇, for paste mixtures made with 0.275 W/C, due to a greater enhancement of particle friction contacts. Meanwhile, the shear thickening performance at a given mini-slump flow increased by using the microfines, given the stronger particle friction contacts caused by the increased flow index of Herschel-Bulkley model. This corresponded to a greater Δ η thic γ ̇ of the pastes. A prediction model of Δ η thic γ ̇ was proposed based on the mechanisms of particle inertia forces and friction contacts. The model can efficiently characterize particle frictional contact interactions in shear thickening regimes by taking into consideration the flow index, particle packing density, and solid volume fraction, regardless of the W/C and the content and type of microfines.